PREVALENCE OF HEPATIC STEATOSIS AMONG CHILDREN AND ADOLESCENTS WITH CYSTIC FIBROSIS AND ITS ASSOCIATION WITH NUTRITIONAL STATUS - Amanda Oliva Gobato; Ana Carolina Junqueira Vasques; Antonio Fernando Ribeiro; Roberto Massao Yamada; Gabriel Hessel (Revista Paulista de Pediatria)
ABSTRACT Objective: To determine the prevalence of hepatic steatosis (HS) in children and adolescents with cystic fibrosis (CF) and associate it with nutritional status. Methods: Cross-sectional study with children and adolescents with CF diagnosis. Weight and height were used to calculate the body mass index (BMI) and subsequent classification of the nutritional status. The midarm circumference (MAC), triceps skinfold thickness (TSF) and midarm muscle circumference (MAMC) were used to evaluate body composition. Abdominal ultrasonography was performed for diagnosis of HS. The statistical tests used were Student’s t test, Mann-Whitney test and chi-square test with significance level of 5%. Results: 50 patients with CF were evaluated, 18 (36%) were diagnosed with HS (Group A) and 32 (64%) without HS (Group B). The mean age of Group A was 13,2±4,9 years old and Group B 11,7±4,9; for BMI, the value for Group A was 18,0±4,1 and Group B was 15,7±3,8; the TSF of Group A was 8,4±3,5 mm and Group B was 7,0±2,5 mm. For these variables, there was no significant difference between the groups. The mean of MAC and MAMC differed significantly between the groups, being higher in the HS group, with p values of 0,047 and 0,043. Conclusions: The frequency of HS in patients with CF is high and it is not related to malnutrition, according to the parameters of BMI, TSF and MAMC. The values of MAC and MAMC indicated a greater reserve of muscle mass in patients with HS.